HABITAT PREFERENCES AND ROOST SITE SELECTION OF Rhinopoma hardwickii Gray, 1831 IN NORTHWESTERN, PAKISTAN - F. U. Rahman; F. Perveen; T. Rauf; M. Salim; Z. Ali; S. Khan; M. S. Yar; N. I. Khan (Journal of Animal and Plant Sciences, 2015)
Present study on habitat characteristics of Rhinopoma hardwickii was conducted in Charsadda district Khyber Pakhtunkhwa for a period of two years extending from May 2011 to July 2013. A bat roost of R. hardwickii was 0 ’ ’’ 0 observed in forest Plantation at Menawrai Baba Shrine (71 52 32.84 E 34 09 ’ 12.39 ’’N), having more than 70 bats, where 5 pups and 3 lactating mothers were also present. Characteristically this roost was present in mulberry tree, Morus alba within a depth of half meter, at a height of 3 meter at breast height. This tree was about 7 meter long, with 1/2 meter diameter. This roost was located within the forest where various plant species including wild fig, Ficus palmate; white cedar, Melia azedarack; paper mulberry, Brousonetia papyrifera; black mulberry, Morus nigra; white mulberry, Morus alba; Indian jujube, Zizipus mauritania; blue gum, Eucalyptus globules; babul, acacia Arabica and commonly used as roosts by Pteropus giganteus at three sites. The black poplar, Populus nigra was the most abundant, while wild fig; Ficus palmate were the least abundant of all species. This paper will help in documenting new information regarding habitats and occurrence of R. hardwickii in Khyber Pakhtunkhwa and will add new distribution map to the bats of Pakistan. Further study about their status and biology is needed. can maintain water balance in their bodies, and like to
Keywords: Chiroptera; Bat; Habitat; Roost site; Rhinopoma hardwickii.